In Situ Polymer Gel Electrolyte in Boosting Scalable Fibre Lithium Battery Applications - Luo, Jie; Zhang, Qichong (Nano-Micro Letters, 2024)
The poor interfacial stability not only deteriorates fibre lithium-ion batteries (FLBs) performance but also impacts their scalable applications. To efficiently address these challenges, Prof. Huisheng Peng team proposed a generalized channel structures strategy with optimized in situ polymerization technology in their recent study. The resultant FLBs can be woven into different-sized powering textiles, providing a high energy density output of 128 Wh kg-1 and simultaneously demonstrating good durability even under harsh conditions. Such a promising strategy expands the horizon in developing FLB with particular polymer gel electrolytes, and significantly ever-deepening understanding of the scaled wearable energy textile system toward a sustainable future. Highlights: 1 Stable interfaces were successfully achieved through designing channel structures in electrodes to sufficiently incorporate polymer gel electrolyte fabricated through in situ polymerization. 2 The resultant fibre lithium battery (FLB) demonstrated superior energy density output of 128 Wh kg−1 and enabled scalable production capability. 3 Such high-performance FLBs presented prospect applications in diverse scenarios, for example, firefighting, space exploration, and human–computer interaction, even under harsh environments.